Kekuatan Eksekutorial Sertifikat Jaminan Fidusia Pasca Putusan Mahkamah Konstitusi Nomor: 18/PUU-XVII/2019 Dan Putusan Mahkamah Konstitusi Nomor: 2/PUU-XIX/2021 - Nabila, Syadzwina Hindun (PATTIMURA Legal Journal, 2022)
Introduction: The Fiduciary Guarantee Certificate has the same executorial power as court decisions that have permanent legal force. Execution through a public auction of the object of Fiduciary Security without going through a court. Purposes of the Research: The Purpose Of This Study Is To Answer The Legal Review On The Executorial Power Of Fiduciary Certificates Post-Decision Of The Constitutional Court Number: 18/PUU-XVII/2019 And The Decision Of The Constitutional Court Number: 2/PUU-XIX/2021. Methods of the Research: This study uses a normative juridical method by using a statutory approach and a conceptual approach. Results Originality of the Research: The execution of fiduciary guarantees is carried out when there is an agreement regarding the breach of contract and the willingness of the debtor to surrender the object that is the object of the fiduciary. If there is no agreement regarding the breach of contract and the debtor does not submit the object of collateral voluntarily, then the execution procedure of the fiduciary guarantee is carried out the same as the execution of a court decision that has permanent legal force, namely by submitting a request for execution to the district court. In addition, breach of contract also cannot be determined unilaterally. There must be an agreement regarding the breach of contract/default determined by both parties or on the basis of legal remedies (lawsuits) stating that one of the parties has defaulted.